Tests of a Partial Adjustment Model of Financial Ratios - WU, Chunchi (Institutional Knowledge at Singapore Management University, 1992)
This article considers the formation of expectations in the financial ratio adjustment. An empirical model consistent with the rational-expectations hypothesis is formulated to analyze the dynamic adjustment pattern of financial ratios. The nonlinear regression method is used to estimate the parameters of the rational-expectations model and to test the validity of rationality. The empirical results show that the rational-expectations model explains the dynamic adjustment of financial ratios reasonably well. The results also show that the rational-expectations model provides a more efficient framework than the simple partial adjustment model for predicting the future ratios.